A lifestyle intervention study targeting individuals with low socioeconomic status of different ethnic origins: important aspects for successful implementation - Dorit Teuscher; Andrea J. Bukman; Marleen A. van Baak; Edith J. M. Feskens; Reint Jan Renes; Agnes Meershoek (BMC, 2017)
Abstract Background Evaluation of the implementation process of trials is important, because the way a study is implemented modifies its outcomes. Furthermore, lessons learned during implementation can inform other researchers on factors that play a role when implementing interventions described in research. This study evaluates the implementation of the MetSLIM study, targeting individuals with low socioeconomic status of different ethnic origins. The MetSLIM study was set up to evaluate the effectiveness of a lifestyle programme on waist circumference and other cardio-metabolic risk factors. The objective of this evaluation was to identify components that were essential for the implementation of the MetSLIM study and to inform other researchers on methodological aspects when working with inadequately reached populations in health research. Methods In this evaluation study the experiences of health professionals, study assistants, a community worker and regional research coordinators involved in the MetSLIM study were explored using semi-structured interviews. Questionnaires were used to evaluate participants' satisfaction with the lifestyle intervention. Results Our analyses show that a flexible recruitment protocol eventually leads to recruitment of sufficient participants; that trust in the recruiter is an important factor in the recruitment of individuals with low socioeconomic status of different ethnic origins; and that health professionals will unavoidably shape the form of intervention activities. Furthermore, our evaluation shows that daily practice and research mutually influence each other and that the results of an intervention are a product of this interaction. Conclusions Health promotion research would benefit from a perspective that sees intervention activities not as fixed entities but rather as social interaction that can take on numerous forms. Analysing and reporting the implementation process of studies, like in this evaluation, will allow readers to get a detailed view on the appropriateness of the (intended) study design and intervention for the targeted population. Evaluation studies that shed light on the reasons for adaptations, rather than describing them as deviation from the original plan, would point out methodological aspects important for a study's replication. Furthermore, they would show how various factors can influence the implementation, and therewith initiate a learning cycle for the development of future intervention studies. Trial registration Netherlands Trial Register NTR3721 (since November 27, 2012).